Pusat Sumber Belajar Matematika Berbasis Website Untuk Meningkatkan Mutu Proses Pembelajaran Matematika - Junaidi, Junaidi; Yulis Tyaningsih, Ratna; Sripatmi, Sripatmi (FKIP Universitas Mataram, 2024)
Limited access to printed materials, lack of interaction, and lack of multimedia-based learning media are significant problems, especially in remote areas such as NTB. In addition, the situation is further complicated by the limitations of infrastructure, internet connections, and teachers' technological capabilities. The purpose of this study is to create a web-based Learning Resource Center (PSB) that utilizes technology to support learning and offer interactive teaching materials. Needs analysis, PSB structure development, guideline preparation, and validation and usability test are all methods used to conduct this study. The inability of technology, the limitations of infrastructure, and the effects of print media on the environment are the main problems identified. Interactive teaching materials, teacher training, wider access to learning materials, and web-based multimedia are some of the solutions that come to mind. The results show that the web-based PSB can function as a learning resource center and support the development of technology-based teaching materials, learning systems, and multimedia. This PSB also provides facilities such as multimedia labs, digital libraries, and access to interactive teaching materials, which improve the quality of learning. So, web-based PSBs help support technology learning, overcome limited access to teaching materials, and improve the quality and efficiency of education, especially in areas with limited infrastructure.